2008
DOI: 10.1007/s10592-008-9693-z
|View full text |Cite
|
Sign up to set email alerts
|

Statistical power for detecting genetic divergence—organelle versus nuclear markers

Abstract: Statistical power is critical in conservation for detecting genetic differences in space or time from allele frequency data. Organelle and nuclear genetic markers have fundamentally different transmission dynamics; the potential effect of these differences on power to detect divergence have been speculated on but not investigated. We examine, analytically and with computer simulations, the relative performance of organelle and nuclear markers under basic, ideal situations. We conclude that claims of a generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
0
56
3
Order By: Relevance
“…Although divergent F ST values gleaned from mitochondria are generally expected to be higher and easier to detect than nuclear F ST because of mtDNA's haploid nature and uniparental inheritance [32], the analyses used in this study show marker divergences to be attributable to sex-biased dispersal rather than differences in N e . First, the large numbers of highly polymorphic markers used in this study lend considerable power to discerning genetic structure at nuclear loci, power that is equal to or greater than mtDNA.…”
Section: Discussionmentioning
confidence: 71%
“…Although divergent F ST values gleaned from mitochondria are generally expected to be higher and easier to detect than nuclear F ST because of mtDNA's haploid nature and uniparental inheritance [32], the analyses used in this study show marker divergences to be attributable to sex-biased dispersal rather than differences in N e . First, the large numbers of highly polymorphic markers used in this study lend considerable power to discerning genetic structure at nuclear loci, power that is equal to or greater than mtDNA.…”
Section: Discussionmentioning
confidence: 71%
“…Several pairwise comparisons using mtDNA were statistically significant (Supplementary Appendix 2), indicating that mtDNA can be a powerful marker, even at low levels of nuclear divergence (Hoarau et al, 2004;Larsson et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that organelle markers such as mtDNA may be more powerful for detecting differentiation in recently diverged populations and especially when migration among populations is relatively high (Larsson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of differentiation are also unlikely to be due to use of a single locus (mtDNA), as studies have demonstrated that when mtDNA variation is high (as in the present case), this locus may approximate or outperform multiple locus markers in terms of power to detect population structure (Larsson et al 2009;Schmidt et al 2011). Low levels of differentiation are not attributable to a lack of power in the analysis as power simulations demonstrated that very low F STs could be detected with our sampling design.…”
Section: Discussionmentioning
confidence: 54%